Inter-temporal variation in the illiquidity premium - Jensen, Gerald R.; Moorman, Theodore (Journal of Financial Economics, 2010)
We find evidence of a systematic link between monetary conditions and inter-temporal variation in the price of liquidity. Specifically, following an expansive monetary policy shift, funding conditions improve and market-wide liquidity increases, which is especially beneficial for illiquid securities. The improved liquidity and funding conditions reduce the returns required for holding illiquid securities. Consequently, illiquid stocks experience relatively large price increases when monetary conditions become expansive, and thus, the measured return spread between illiquid and liquid stocks expands substantially. Overall, our evidence supports the claim that the price of asset liquidity is dependent on monetary conditions.